Sustainable leadership in private universities in Gaza Governorate in light of the requirements of the Fourth Industrial Revolution (Palestine Technical College Journal for Research and Studies, 2023)
The study aimed to identify the degree of sustainable leadership practice in the private Palestinian universities in the governorates of Gaza in the light of the requirements of the fourth industrial revolution from the point of view of its academic leaders, and to reveal whether there were statistically significant differences at the level of significance (α ≥ 0.05) between the average degrees of the sample members' estimate of the degree of The practice of sustainable leadership in the private Palestinian universities in the governorates of Gaza in the light of the requirements of the fourth industrial revolution due to: (service years and educational qualification). The descriptive survey approach was used and a questionnaire was built consisting of (23) items divided into four main dimensions: (human resource development, long-term orientation, creativity, and social responsibility). After verifying its validity and reliability, it was applied using Comprehensive inventory method on (121) academic leaders.The findings of the study showed that the degree of practicing sustainable leadership in the private Palestinian universities in the Gaza governorates was "high" , with a relative weight (72.4%).The results also showed that there were no statistically significant differences at the significance level (α < 0.05) between the average scores of the sample members' estimation of the degree of practicing sustainable leadership in private Palestinian universities in the light of the requirements of the fourth industrial revolution were attributed to variables of : (service years and educational qualification). The study recommended organizing training courses to empower faculty members and provide them with the knowledge and skills that help them to employ modern digital means in the educational process.
Keywords: Sustainable leadership; the Fourth Industrial Revolution; private universities; Gaza governorates